Coin pica‐induced gastric perforation resulting from ingestion of 1, 894 coins, 8 kg in total: case report and review of published works. Issue 2 (24th October 2017) - Sekiya, Kosuke; Mori, Shusuke; Otomo, Yasuhiro
Abstract : Case: Pica is common among patients with psychiatric disorders, but only a few cases regarding coin pica have been reported. A 51‐year‐old man with depression complaining of fatigue was found to have numerous coins in the esophagus and the stomach on X‐rays. He had a peritoneal sign and underwent an emergency laparotomy. Outcome: The surgical findings showed perforation on the anterior wall of the gastric body and coins in the stomach, which were removed manually, followed by an omental patch. Residual coins in the esophagus were removed by endoscopy. The coins totaled 1, 894, weighing 8, 076 grams. The patient was then diagnosed as schizophrenic. He was asymptomatic for metal toxicity and was finally transferred to a psychiatric hospital. Conclusion: This pica case is the first to show coin pica can lead to gastric perforation, and also reports the largest amounts of coins ingested by a person to date. Abstract : A 51‐year‐old man with schizophrenia, who was found to have numerous coins in the esophagus and stomach, underwent an emergency operation for peritonitis. A few cases regarding coin pica have been reported. This case was the first showing gastric perforation and the largest number of ingested coins.